Challenges of vocational education in Iceland: Access to higher education - Eiríksdóttir, Elsa (Menntavísindasvið Háskóla Íslands, 2022)
One of the key challenges to vocational education and training (VET) at upper secondary education level is how to change the perspective that it represents a dead-end pathway. This challenge is often discussed in the context of how to increase the standing of VET and refers to efforts in increasing VET participation (Billett, 2020; Elsa Eiríksdóttir et al., 2018; OECD, 2013a). In Iceland, only about 15% of young people choose VET in upper secondary schools and educational authorities have long emphasized the need for action (Mennta- og menningarmálaráðuneytið [Ministry of Education, Science and Culture], 2014). Providing VET graduate access to higher education (HE) is often mentioned as an important measure – especially with increased expansion and participation in HE (Jón Torfi Jónasson, 1998, 2003). The goal of the article is to look at how the access of VET graduates to HE has developed over the past two decades in Iceland, both in terms of structure and regulations governing the education system, as well as opportunities for students and their participation. The development of VET students’ access to HE is considered in terms of: (1) preparation for HE at upper secondary school level, and (2) changes made to the HE education level to accommodate those graduating from VET programmes (VET graduates).Until 2021, a matriculation examination was required for university admission in Iceland and while academic programmes at upper secondary schools typically end with matriculation, VET programmes do not. Typical VET programmes take four years to complete and if matriculation is sought, it usually means additional time at upper secondary school. In the years 2008 to 2011 the regulatory framework of upper secondary education was reformed, and a new national curriculum introduced. Decentralization of curriculum design, and a disengagement of the type of qualifications (e.g., matriculation examination) and type of programme (academic, vocational, or arts) were part of this reform. These changes created the opportunity ...